Rites of Passage: Flow of Gifts - Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2011)
This paper aims to explore how gifts are connected with the sanskars, rites of transition or rite of passage. I have discussed how gifts are connected culturally in the context of rites of transitions, in order to systematically search for the different contexts that influence those who act out these events, where people are obliged to give gift as well as oblige to receive, if one does not receive it becomes insult of giver and develops conflicting relationship. Giving gift in this context follows the generalized reciprocity, and flows in a certain direction, but its latent meaning is to keep strong social bond between kin groups and ancestors. Obligation for giving gift and return are closely associated with distance of kinship. Gift is obliged to give and receive sometimes not necessarily return immediately, which also depends upon kin ties. Most obligatory gift should be made to sister and their children. Rites of passage is not only associated with liminality and unstructure social status also with flow of gift. Giving gift in ritual context is to avoid inauspiciousness. Important dimension of gift giving, receiving and returning all are matter of morality, honor, and prestige. Rituals and women are medium of exchange of gift. In general gifts and forms, material condition and social relation of exchange are linked to kinship rank and in the context of ritual. Keywords: reciprocity; Argali Magars; sanskar; rituals; morality DOI: 10.3126/dsaj.v4i0.4516 Dhaulagiri Journal of Sociology and Anthropology Vol.4 2010 pp.111-128